NATO's two percent illusion: Germany needs to encourage greater efficiency within the alliance - Christian Mölling (Stiftung Wissenschaft und Politik (SWP), 2014)
In order to plug the gaps in NATO's defence capabilities, Europeans - and Germans especially - need to increase defence spending to 2% of gross domestic product (GDP). The United States especially has been insistent on compliance with this target, which was set in 2002. But this benchmark has long been known to be an illusion, one many European NATO member states are neither willing nor able to implement. In any case, the 2% benchmark focuses on expenditures rather than improved outcomes. The federal government should develop its own concept of how NATO can apply its financial resources more efficiently - and it could use output criteria and specific contributions to convey its concept. (SWP-Comments)
Keywords: 320